Effectiveness of Health Education on the Behavioral Outcomes of Students at SMP IT Assajadah - Tarbiyah Nurjanah; Rizta, Sri Utami (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This study examined the effectiveness of personal hygiene health education in improving students’ health knowledge and health-related behaviors at SMP IT As Sajadah. A quantitative pre-test–post-test experimental design was employed involving 60 students who participated in interactive personal hygiene education sessions incorporating lectures, discussions, and demonstrations. Data were collected using standardized questionnaires to assess health knowledge and health behaviors, complemented by systematic behavioral observations focusing on personal hygiene practices. Pre- and post-intervention differences were analyzed using paired t-tests. The results demonstrated a statistically significant increase in students’ health knowledge, with mean scores rising from 65.23 to 82.76 (p < 0.001). Observational findings revealed consistent positive behavioral changes, particularly in personal hygiene practices, including improved self-cleanliness, regular handwashing, healthier daily routines, and more disciplined use of school facilities. Behavioral score analysis further confirmed a significant effect of personal hygiene health education on students’ health-related behaviors (p < 0.05). These findings provide robust empirical evidence supporting the effectiveness of interactive, school-based personal hygiene health education in promoting positive behavioral outcomes. From a managerial perspective, the results offer practical guidance for school administrators, educators, and health program managers in evidence-based decision-making, program refinement, and strategic management of school-based personal hygiene education initiatives, particularly within Islamic educational contexts